Metal-insulator Phase Diagram for the Fully Diagonal Disordered Hubbard Model at Half-filling - Tuan, Hoang Anh; Yen, Nguyen Thi Hai (Communications in Physics, 2016)
The electronic properties of strongly correlated systems with binary type of disorder are investigated using the coherent potential approximation. For half-filled system, two transitions from a band insulator via a metallic state to a Mott insulator are found with increasing the correlation strength of only one of the constituents. Our phase diagram is consistent with those obtained by the dynamical mean field theory.